PENINGKATAN KETERAMPILAN MENULIS PUISI SISWA DENGAN MODEL MIND MAPPING DI KELAS V SD NEGERI 06 III KOTO KABUPATEN TANAH DATAR - fitriah, ledi; sukma, elfia; indrawati, tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research to describe the improvement of poetry writing skills of students with mind mapping models in class V SDN 06 III Koto, Tanah Datar. This classroom action research was conducted in two cycles by applying both qualitative and quantitative approaches. The subjects of the research was teachers and 18 students in class V of SDN 06 III Koto. The results of the research indicated that : a) the score before writing stage teacher activity of the first cycle was 75% and second cycle was 100% , student activities of the first cycle was 75% , and second cycle was 100%, grade average of the first cycle was 73, and second cycle was 93, b) the score of writing stage, the teacher activities of the first cycle was 75%, and second cycle was 87%, student activities of first cycle was 75% , and second cycle was 100%, average grade of the first cycle was 78, and second cycle was 87, c) post-writing stage teacher activities of the first cycle was 75%,  and second cycle was 100% , student activities of the first cycle was 75%,  and second cycle was 93% , grade average in cycle I 73, and second cycle was 93. Keywords: Mind Mapping Model, Poetry Writing